Significantly improving mechanical properties of CF/PAI composites: the influence of interfacial modification coupled with post heat treatment - Fang Zhou; Zhenbo Zhao; Deqi Jing; Xinghua Zhang; Peng Wang; Weiguo Su; Shouchun Zhang (Journal of Materials Research and Technology, 2023)
Carbon fiber reinforced polyamide-imide (CF/PAI) composites are potential candidates for high temperature applications under high stress conditions. However, the structure–property relationships of CF/PAI are not clear. This work presented an experimental investigation into the influence of interfacial modification and heat treatment on the microstructures and mechanical properties of CF/PAI composites. The CF/PAI interfacial interactions were improved by the combined effect of chemical bonding between the PAI-compatible sizing and CF as well as hydrogen bonding between the sizing and matrix. Meanwhile, heat treatment enhanced the modulus of matrix, which was beneficial to stress transfer in the interfacial region. Therefore, the interlaminar shear strength (ILSS), flexural strength, and flexural modulus of RS0.6-CF/PAI composites (the concentration of PAI-compatible sizing agent was 0.6 wt%) were remarkably improved by 81.3%, 23.7%, and 39.1% compared with the control specimen. Microstructure examinations of modified and unmodified CF/PAI composites showed that both interfacial modification and heat treatment played an important role in the transitions of failure mode under interlaminar shear loading and flexural loading. These findings provide an effective method to tailor the microstructures of CF/PAI composites for achieving the desired properties.